2019
DOI: 10.1108/jbim-10-2018-0287
|View full text |Cite
|
Sign up to set email alerts
|

Coopetition: a fundamental feature of entrepreneurial firms' collaborative dynamics

Abstract: Purpose This paper aims to explore coopetition as a fundamental feature of the collaborative dynamics inherent in entrepreneurial ventures. The authors present a conceptual model and definition of entrepreneurial coopetition, the latter being explained as entrepreneurial involvement in simultaneous cooperative and competitive interactions with business network actors in a relational environment. Design/methodology/approach Using the micro-brewing industry in a Southern State in the USA, as an empirical base,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 76 publications
0
44
0
Order By: Relevance
“…Over the past twenty years, there has been a growing interest surrounding coopetition-oriented behaviours (also known as coopetition activities or coopetition strategies) throughout the broader business-to-business marketing literature (Bengtsson and Kock, 2000; Rusko, 2011; Park et al , 2014; Bengtsson and Raza-Ullah, 2016; Felzensztein et al , 2018; McGrath et al , 2019; Lascaux, 2020). These activities are described as being the interplay between cooperation and competition, whereby rival organisations (especially smaller-sized entities) share resources (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past twenty years, there has been a growing interest surrounding coopetition-oriented behaviours (also known as coopetition activities or coopetition strategies) throughout the broader business-to-business marketing literature (Bengtsson and Kock, 2000; Rusko, 2011; Park et al , 2014; Bengtsson and Raza-Ullah, 2016; Felzensztein et al , 2018; McGrath et al , 2019; Lascaux, 2020). These activities are described as being the interplay between cooperation and competition, whereby rival organisations (especially smaller-sized entities) share resources (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it could be that the coopetition-oriented mindset–coopetition-oriented behaviours link is affected by organisations’ degree of internationalisation. Collectively, these research gaps signify that work should be undertaken to unpack this association to identify how firms can best-manage the interplay between cooperation and competition (extending Brandenburger and Nalebuff, 1996; Tidstrom, 2009; Mattsson and Tidstrom, 2015; Leite et al , 2018; McGrath et al , 2019). More formally, under resource-based theory and the relational view (Barney, 1991; Dyer and Singh, 1998; Lavie, 2006; Dyer et al , 2018), the objective of this current study is to evaluate the relationship between a coopetition-oriented mindset and coopetition-oriented behaviours under the moderating roles of industry experience and degree of internationalisation.…”
Section: Introductionmentioning
confidence: 99%
“…Coopetition with the paradox perspective challenges the traditional resolution of a trade-off because it manages opposites, thus showing a synergistic consequence of the cooperative and competitive forces Schad et al, 2016;McGrath et al, 2019). It is, therefore, crucial to understand that coopetition is not simply the addition of the two separate continuums (Bengtsson et al, 2010) because cooperation and competition mutually define and depend on each other (Schad et al, 2016); meanwhile, the characteristic of contradiction existing in the opposites will bring tensions that lead to the instability of the inter-firm relationships but can also stimulate partners' effectiveness and creativity (Chiambaretto and Fernandez, 2016).…”
Section: Conceptual Background and Hypothesesmentioning
confidence: 99%
“…That is, companies can supplement their unique selling points (points-of-differentiation) by harnessing rivals' resources and capabilities to enhance their customer satisfaction performance (Felzensztein et al, 2018). Thus, coopetition can assist small firms to satisfy the wants and needs of their target markers in ways that would be more difficult to achieve through their own assets (McGrath et al, 2019;O'Dwyer et al, 2011). Accordingly, it follows that:…”
Section: Coopetition and Customer Satisfaction Performancementioning
confidence: 99%
“…The empirical context for this current article was the New Zealand wine industry. Wineproducing countries (as well as other firms within the global alcohol market) are wellknown for hosting the above-mentioned factors (Felzensztein et al, 2014;Mathias et al, 2018;McGrath et al, 2019). For example, Crick (2018) found that wine producers are cooperative through lending equipment, such as expensive machinery that is needed only once a year (e.g., during the harvest).…”
Section: Population Of Interestmentioning
confidence: 99%